KONDISI KUALITAS AIR SUNGAI CILIWUNG DI WILAYAH DKI JAKARTA DITINJAU DARI PARAMATER ORGANIK, AMONIAK, FOSFAT, DETERJEN DAN BAKTERI COLI - Yudo, Satmoko (Center for Environmental Technology, 2010)
Jakarta city has 13 rivers one of which is Ciliwung river. It flows across the city amid a lot of dense housing, slums and villages. As a result the river is experiencing the most severe pollution compared to other rivers that flow in Jakarta. To find out how much pollution in the Ciliwung river, this paper will discuss several pollutant parameters such as, BOD, COD, ammonia, phosphates, detergent and coli bacteria. Overall, that the concentrations of these parameters continue to increase annually, this causing pollution in the Ciliwung river higher.Ã‚Â Keywords : Ciliwung rivers, water pollution from domestic wastewater, river water quality, organic parameters, ammonia, phosphates, detergent and coli bacteria.